56h-712=-34h-136

Combine 56 and h.

5h6-712=-34h-136

Combine h and 34.

5h6-712=-h⋅34-136

Move 3 to the left of h.

5h6-712=-3h4-136

5h6-712=-3h4-136

Add 3h4 to both sides of the equation.

5h6-712+3h4=-136

To write 5h6 as a fraction with a common denominator, multiply by 22.

5h6⋅22+3h4-712=-136

To write 3h4 as a fraction with a common denominator, multiply by 33.

5h6⋅22+3h4⋅33-712=-136

Write each expression with a common denominator of 12, by multiplying each by an appropriate factor of 1.

Multiply 5h6 and 22.

5h⋅26⋅2+3h4⋅33-712=-136

Multiply 6 by 2.

5h⋅212+3h4⋅33-712=-136

Multiply 3h4 and 33.

5h⋅212+3h⋅34⋅3-712=-136

Multiply 4 by 3.

5h⋅212+3h⋅312-712=-136

5h⋅212+3h⋅312-712=-136

Combine the numerators over the common denominator.

5h⋅2+3h⋅312-712=-136

Combine the numerators over the common denominator.

5h⋅2+3h⋅3-712=-136

Simplify the numerator.

Multiply 2 by 5.

10h+3h⋅3-712=-136

Multiply 3 by 3.

10h+9h-712=-136

Add 10h and 9h.

19h-712=-136

19h-712=-136

19h-712=-136

Multiply both sides of the equation by 12.

19h-7=-136⋅12

Remove parentheses.

19h-7=-136⋅12

Cancel the common factor of 6.

Move the leading negative in -136 into the numerator.

19h-7=-136⋅12

Factor 6 out of 12.

19h-7=-136⋅(6(2))

Cancel the common factor.

19h-7=-136⋅(6⋅2)

Rewrite the expression.

19h-7=-13⋅2

19h-7=-13⋅2

Multiply -13 by 2.

19h-7=-26

19h-7=-26

Add 7 to both sides of the equation.

19h=-26+7

Add -26 and 7.

19h=-19

19h=-19

Divide each term in 19h=-19 by 19.

19h19=-1919

Cancel the common factor of 19.

Cancel the common factor.

19h19=-1919

Divide h by 1.

h=-1919

h=-1919

Divide -19 by 19.

h=-1

h=-1

Solve for h 5/6h-7/12=-3/4h-13/6